2020
DOI: 10.1038/s41598-020-73781-y
|View full text |Cite
|
Sign up to set email alerts
|

Tilapia lake virus downplays innate immune responses during early stage of infection in Nile tilapia (Oreochromis niloticus)

Abstract: Tilapia lake virus (TiLV) causes high mortality and high economic losses in tilapines. We describe an experimental challenge study focusing on early post challenge innate immune responses. Nile tilapia (Oreochromis niloticus) were infected with 105 TCID50/mL TiLV intraperitoneally, followed by virus quantification, histopathology and gene expression analysis in target (brain/liver) and lymphoid (spleen/headkidney) organs at 3, 7, 12, 17, and 34 days post challenge (dpc). Onset of mortality was from 21 dpc, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
36
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 47 publications
9
36
0
2
Order By: Relevance
“…Various factors and mechanisms such as differences in innate immunity or host cell permissiveness are likely involved in weight-dependent susceptibility to TiLV infection. Prior to this study, a different expression of cytokines and immune-related genes was reported in tilapia during TiLV infection (Mugimba et al, 2020;Pierezan et al, 2020;Sood et al, 2021). For example, Mugimba et al (2020) showed that the TiLV viral load and expression of immune-related genes were inversely correlated in the brain and spleen of infected fish.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Various factors and mechanisms such as differences in innate immunity or host cell permissiveness are likely involved in weight-dependent susceptibility to TiLV infection. Prior to this study, a different expression of cytokines and immune-related genes was reported in tilapia during TiLV infection (Mugimba et al, 2020;Pierezan et al, 2020;Sood et al, 2021). For example, Mugimba et al (2020) showed that the TiLV viral load and expression of immune-related genes were inversely correlated in the brain and spleen of infected fish.…”
Section: Discussionmentioning
confidence: 88%
“…Prior to this study, a different expression of cytokines and immune-related genes was reported in tilapia during TiLV infection (Mugimba et al, 2020;Pierezan et al, 2020;Sood et al, 2021). For example, Mugimba et al (2020) showed that the TiLV viral load and expression of immune-related genes were inversely correlated in the brain and spleen of infected fish. Alternatively, a mechanism to facilitating viral persistence in younger fish e.g., production of immunosuppressive cytokines, could play a role in suppressing the host response to TiLV.…”
Section: Discussionmentioning
confidence: 88%
“…TiLV has a linear, negative-sense single-strand RNA genome with 10 segments and about 10.323 kb in total length (22,23). Interestingly, a high level of TiLV was observed in the brain of infected tilapia (23,25), and this was correlated with the clear histopathological changes (23) and activation of the expression of genes involved in the antiviral immune response in the tilapia brain (25,26). We recently described the TiLV infection model in adult and larvae of zebrafish (27,28), and our virus tropism study revealed that in adult fish the highest viral load of TiLV was found in the brain (27).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the presence of the TiLV genomic RNA in the infected brain has also been determined by in situ hybridization (Bacharach et al., 2016; Dong et al., 2017). However, these findings were limited at suggesting that the brain is one of the target tissues for transcription and replication of the virus (Mugimba et al., 2020). In fact, the fish brain divides into different regions and each part is responsible for certain functions (Table 1) (Roberts & Ellis, 2012; Sado et al., 2020).…”
Section: Introductionmentioning
confidence: 99%